Border control: a membrane-linked lnteractome of arabidopsis - Jones, Alexander M.; Xuan, Yuanhu; Xu, Meng; Wang, Rui-Sheng; Ho, Cheng-Hsun; Lalonde, Sylvie; You, Chang Hun; Sardi, Maria I.; Parsa, Saman A.; Smith-Valle, Erika; Su, Tianying; Frazer, Keith A.; et al. (Science, 2014)
Cellular membranes act as signaling platforms and control solute transport. Membrane receptors, transporters, and enzymes communicate with intracellular processes through protein-protein interactions. Using a split-ubiquitin yeast two-hybrid screen that covers a test-space of 6.4 × 106 pairs, we identified 12,102 membrane/signaling protein interactions from Arabidopsis. Besides confirmation of expected interactions such as heterotrimeric G protein subunit interactions and aquaporin oligomerization, >99% of the interactions were previously unknown. Interactions were confirmed at a rate of 32% in orthogonal in planta split-green fluorescent protein interaction assays, which was statistically indistinguishable from the confirmation rate for known interactions collected from literature (38%). Regulatory associations in membrane protein trafficking, turnover, and phosphorylation include regulation of potassium channel activity through abscisic acid signaling, transporter activity by a WNK kinase, and a brassinolide receptor kinase by trafficking-related proteins. These examples underscore the utility of the membrane/signaling protein interaction network for gene discovery and hypothesis generation in plants and other organisms.